Relationship Between Interleukin -33( IL-33) and C- Reactive Protein in Iraqi Women Patients with Celiac Disease. - Abass, Eiman A.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Interleukin -33 is a new member of the IL-1 superfamily of cytokines that is expressed mainly by stromal cells.Its expression is upregulated following pro-inflammatory stimulation. Aim of the present study was to assess the serum IL-33 level and its relationship with inflammatory biomarker CRP  in Iraqi females patients with celiac disease.  Thirty five patients with celiac disease (CD)  and thirty healthy individuals as control group  were enrolled in this study,their age ranged (20-35) year.Anti-Gliadin IgA ,IgG and Anti-Tissue IgA ,IgG were estimated in all subjects as  diagnostic parameters .ESR and CRP were assayed as inflammatory biomarkers. IL-33 was determined in patients and control groups.  The results of the present study revealed a highly significant increase in anti-gliadin (IgA , IgG) , anti-tissue (IgA, IgG) ,ESR,and CRP levels in CD patients compared to control. While no significant increase in  IL-33  level in CD  patients  compared to control was found. In conclusion, IL-33 could be considered as a biomarker for Celiac Diseases, and it is correlated positively with inflammatory biomarker"CRP" in Iraqi women patients with CD.